Ipar adalah Maut: Analisis Semiotika Representasi Pengkhianatan dan Keretakan Rumah Tangga - Bunga Rahma Sindisa (Jurnal Nomosleca, 2026)
Film is a reflection of social reality capable of constructing complex phenomena such as infidelity into a system of signs. This study aims to uncover the representation of betrayal and household breakdown in the film "Ipar Adalah Maut" through visual and verbal sign analysis. The main issue raised is how the presence of those closest to the family can pose a threat to domestic stability. The method used is descriptive qualitative with Roland Barthes' semiotic analysis approach, which dissects meaning through the levels of denotation, connotation, and myth. The results show that the film presents betrayal not merely as an individual moral lapse, but as a deconstruction of the meaning of "home" from a safe space into a space full of threats. Through visual symbolism, such as the broken expressions of the main character and the transformation of private spaces, the film challenges the myth that family is the safest place. The study concludes that the film reproduces social views on the importance of privacy boundaries within the family. Household breakdown is represented as "death" (maut) that destroys the social structure, the moral authority of the mother figure, and fraternal bonds. These findings contribute to media studies regarding how modern Indonesian cinema naturalizes moral vulnerability within the family institution.